On correlating the modulus of elasticity of stack-bonded flyash brick masonry using impact hammer and compression tests. Issue 4 (20th March 2020) - Verma, Ravi; Basu, Dhiman
Abstract: Possibility of a new framework of characterising (stack-bonded) masonry properties is explored in three steps: (i) estimation of modulus of elasticity through impact hammer test (which is non-destructive and denoted as non-destructive test [NDT]); (ii) correlating the modulus of elasticity using NDT with that computed using typical destructive test (DT); and (iii) empirical relation for other masonry properties, such as compressive strength involving the modulus of elasticity. The second step is the kernel of proposed framework and once that correlation is established, in situ characterisation of masonry properties is possible without requiring any heavy equipment. Fifty-one masonry prisms are constructed using eight varieties of fly ash bricks and four types of mortar. Out of which, 33 samples are tested with impact hammer for the modulus of elasticity and followed by DT for the stress–strain plots. Correlation is developed for the moduli of elasticity computed using DT and NDT. DT is also carried out for the remaining prisms and other properties are correlated with modulus of elasticity of masonry and compressive strength of the constituting brick and mortar. Results indicate the feasibility of proposed framework, which, if adopted, is likely to enable true engineered construction for the small-scaled masonry dwellings in long run.